Rodzicielstwo w postaci maternal gatekeeping. Analiza zjawiska - Kwak, Anna (Uniwersytet Wrocławski. Wydział Nauk Społecznych. Instytut Socjologii, 2021)
Even recent past reveals that mothers are assigned the role of the first, primary caretaker. Nowadays, both parents are expected to participate equally in the matters related to their child. Do mothers give up easily the field that so far has been their domain and perpetuated the ‘old’ social order? The clash between the old approach to parental roles and the new expectations addressed mainly to fathers does not always result in the transition to common and equal participation of the mother and father in the implementation of their parental roles. Behaviors referred to as maternal gatekeeping are of a complex nature. Researchers are trying to understand what determines the willingness of mothers to encourage the fathers in or discourage from engaging in childcare and responsibility for matters related to it. The conducted analysis of the phenomenon is based on theoretical considerations and empirical investigations of researchers who, apart from indicating the disadvantages of maternal gatekeeping, also point to specific family situations justifying this type of behavior.
Keywords: maternal gatekeeping; parental roles; encouraging or discouraging of father